Harsh Words Used by Indonesia Netizens in Social Media - Aknes Grecia; Betharia Sembiring Pandia; Berlin Sibarani (Universitas Negeri Medan, 2023)
The determination of Indonesian netizens had damaged the image of Indonesia as a friendly and polite country as the most disrespectful netizens in Southeast Asia in 2021 and this was not suitable with Indonesian culture which always prioritized politeness. The more development and transparency of social media, the more netizens used harsh words to express their opinion. The use of offensive words on social media was a serious matter and had negative impacts such as damaging self-image to imprisonment. The purpose of this study was to analyze the use of harsh words among Indonesian netizens on various topics. The methodology used in this research was descriptive qualitative. The data was collected by capturing harsh words used by netizens on social media. The results showed that three topics become targets to write harsh words by netizens, namely politics, celebrity, and humanity topics. The number of harsh words found on the political topic is 10 words, while the celebrity topic contains 21 harsh words and 4 harsh words in humanity topic. The word bacot (bullshit) was most often used by netizens to attack politicians with a percentage of 22,2%, selalu merasa jadi korban (playing victim) with a percentage of 14% to attack celebrity and tolol (stupid) in humanity topic. Therefore, through this research some suggestions were directed to Indonesian netizens and stakeholders to maintain Indonesia's culture of good communication while they were on social media.